PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU BRODO DI KOTA BANDUNG - Mochamad Ferdy Ilham Fachrezy; Sherly Artadita (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Brodo is a local shoe brand that has been in the fashion industry for a long time. As time goes by, the use of shoes has become increasingly diverse and adapts to the needs of the wearer. Amid the onslaught of competition between local shoe manufacturers, Brodo is still the choice of consumers. Seeing this situation, this study will analyze and examine the influence of brand image and product quality in influencing purchasing decisions on Brodo shoe products. This study used quantitative methods with the analytical techniques used, namely descriptive analysis and multiple linear regression analysis. Samples were taken using non-probability sampling method, with a total of 150 respondents. The results of research conducted by researchers showed that the variables of brand image, product quality and purchasing decisions on Brodo shoe products were included in the good category. Based on the results of hypothesis testing, it shows that there is a positive and significant influence on brand image and product quality on purchasing decisions on Brodo shoes products either partially or simultaneously. Based on the coefficient of determination, it was found that the effect of brand image and product quality on purchasing decisions for Brodo shoes was 76.7%, while the remaining 23.3% was influenced by other factors not examined in this study.